Safe Transitions for Every Patient (STEP): A Resource Guide for Community Preceptors - Staci Young; Angie Zikos; Jeffrey Morzinski; Linda Meurer (Association of American Medical Colleges, 2012)
Abstract Introduction This resource was designed to prepare and support community preceptors engaged in undergraduate and graduate medical education in the task of enhancing communication and care-transition information. Methods This resource contains an instructional guide, a PowerPoint orientation to care transition curricula, and a toolkit of written materials to remain at the community preceptors' office to be used as a resource for practical prompts and teaching when medical students are present. The toolkit includes a case analysis form, a patient interview form, and a consultation/referral request form. Results This resource was piloted in eight separate sessions with community primary care preceptors. Session evaluations from 45 preceptors utilized a 4-point Likert scale where 4 = strongly agree and 1 = strongly disagree. Preceptors indicated that they would be able to teach students to define care transitions (3.54), list major components of safe transitions (3.60), describe the role that effective transitions have on safe and high-quality patient care (3.69), and how to use the PRIMARY mnemonic for a patient transition (3.27). Discussion Care transitions are a key component of good patient care and poor communication is known to be a major contributor to patient harm. Therefore, this information is designed to enhance teaching in these critical areas.